Use of organic fertilizers and microbial phosphate solubilizers to improve maize plant quality - Mutmainna, Mutmainna (Professorline, 2024)
Maize plants are one of Indonesia's most important food crops, which require nutrients containing sufficient phosphorus (P) for growth. However, soil P availability could be higher due to physical, chemical and biological factors. Therefore, this study investigates the effect of organic fertilizers and phosphate solubilizing agents (MPF) on maize plant quality. This study used a randomized group design with four treatments: no organic fertilizer and MPF (comparison), organic fertilizer only, MPF only and organic fertilizer and MPF. The results showed that treatment with organic fertilizers and MPF positively affected maize plant quality, such as plant height, stalk diameter, number of leaves, leaf area, shoot wet and dry weight, root wet and dry weight, and P. content in plants. This indicates that applying organic fertilizers and MPF can increase soil P availability and P uptake by maize plants. Thus, using organic fertilizers and MPF can be an environmentally friendly and economical alternative to improve the quality of corn plants.